(untitled) (Journal of Parents and Teachers, 1996)
Students’ frustration with conventional teaching methods and the urgency of implementing more dynamic approaches. It criticizes the repetition of content and the overload of tasks, which generate disinterest. It also emphasizes the need to consider students’ voices in order to enrich the educational process.